Growth of Basella alba under different light environments - Brito, Gildeon Santos; Souza, Cristian Martins de; Jesus Neto, Alfredo Teles de; Souza, Girlene Santos de; Santos, Anacleto Ranulfo dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Basella alba L. (Malabar spinach) is a non-conventional food plant (PANC) with high nutritional value and economic potential. Light is a critical factor in plant growth, acting directly on the photosynthetic process. The photoselective meshes combine the physical protection of plants with the selective filtering of solar radiation to promote physiological responses. This work evaluates the growth of B. alba under different light environments. The experiment occurred in a greenhouse at the Center for Agrarian, Environmental and Biological Sciences of the Federal University of Recôncavo da Bahia in a completely randomized design with plots comprising one useful plant and five replications. The plants were grown in three light environments: red ChromatiNet mesh, aluminet-thermo reflective mesh (both with 50% irradiance), and under full sun. The red mesh increased the root dry matter mass and stem diameter. The aluminet mesh increased the average number of leaves by about 50% compared to the plants cultivated under full sun. The results show that the cultivation of B. alba in different light environments promotes morphophysiological changes with positive increments in growth.